Inhibition of N- and L-type Ca2+ channels by the spider venom toxin omega-Aga-IIIA. - Mintz, I M (1991)
omega-Aga-IIIA, an 8.5-kDa peptide toxin isolated from the venom of Agelenopsis aperta, was found to be a highly potent inhibitor of Ca channels in cardiac muscle and in peripheral and central neurons of rats and frogs. Cardiac L-type Ca channels were completely (Kd approximately 0.6 nM) blocked by omega-Aga-IIIA. In sensory neurons, the toxin inhibited most high-threshold Ca current but not T-type Ca current. omega-Aga-IIIA blocked with similar potency (Kd approximately 1.5 nM) both omega-conotoxin GVIA-sensitive and dihydropyridine-sensitive current components but left a fraction (approximately 35%) of high-threshold current that was also resistant to omega-conotoxin and dihydropyridines. The toxin blocks N- and L-type channels with equal potency and therefore may identify a high-affinity binding site common to these two Ca channel types.